Live Streaming: Revolution New in Retail Business Marketing Strategy (Literature Study) - Khoiril Mala, Iva; Kholifah, Leli; Pratikto, Heri; Winarno, Agung; Setyohadi (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose – The post-COVID-19 pandemic has driven digitalization in various aspects of life, one of which is consumer purchasing behavior. With limited mobility and increasingly stringent regulations regarding activities outside the home, including shopping in malls, consumers who previously went to physical stores tend to shop online. This has led to a new revolution in the world of marketing: Live Streaming, a medium that connects businesses with buyers online without the need to visit a physical store. Design/Methods/Approach – This research method uses a literature review system to analyze documents that align with the research focus. Previously, documents were reviewed using Google Scholar, Scopus, and WoS. 50 journals were then identified and filtered, resulting in 13 articles for analysis. Findings – This proves that live streaming can break down the limitations previously imposed by traditional marketing. Retailers cannot ignore the challenges and obstacles faced in using live streaming, such as technical constraints and increasingly fierce online business competition. Research Implications/Limitations – Businesses can consider using a professional host to ensure product and service information is conveyed clearly and easily understood by the audience during live streaming. Originality/Value – Live streaming can help retail business actors to keep up with the times in the form of digitalization, seeing consumer interest in consuming products.